Reformasi Hukum Ketenagakerjaan: Menuju Kesejahteraan Pekerja - Adela Salsabila; Enjum Jumhana; Ade Putri Hanifa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Labour law reform in Indonesia is a strategic step to create welfare for workers in the face of the challenges of globalization and an ever-evolving labour market. With the fast-paced changes in the work environment, along with globalization and technological advancements, it is important to make regulatory adjustments that can effectively protect workers' rights while also considering the needs of employers. This research takes a closer look at the importance of labor law reform in Indonesia, particularly focusing on improving workers' welfare. We use normative legal research methods with statutory and conceptual approaches. The data we collected included relevant laws regarding labor, legal literature, and official documents. The results show that several aspects of labor law in Indonesia still need to be reformed, including the wage system, social security, protection of contract and outsourced workers, and industrial relations dispute resolution mechanisms. We hope that these reforms will pave the way for a more equitable, responsive and adaptable labor law system that can truly improve workers' welfare in a sustainable manner